2012
DOI: 10.1177/1474515112443931
|View full text |Cite
|
Sign up to set email alerts
|

Clinical indicators of ineffective airway clearance for patients in the cardiac postoperative period

Abstract: The results suggest that there are differences between the ineffective airway clearance indicators as accuracy measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
3
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 20 publications
1
25
3
6
Order By: Relevance
“…)–56 years (Sousa et al . ). In studies conducted only with children, the average age ranged from 4·75–28·5 months.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…)–56 years (Sousa et al . ). In studies conducted only with children, the average age ranged from 4·75–28·5 months.…”
Section: Resultsmentioning
confidence: 97%
“…) and adults undergoing cardiac surgery (Sousa et al . ). In the other studies, these defining characteristics showed high values only for sensitivity.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The incidence of IAC in our sample was 49.5%, similar to the findings of Pascoal et al.’s study (), in which this diagnosis was present in 46.73% of the sample. Respiratory impairments are frequent in postoperative patients because of the impairments that result from the surgical procedures (Sousa et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies report that the postoperative period is a risk factor for the development of ineffective airway clearance (IAC) (00031), which is a nursing diagnosis from the NANDA‐I (Pascoal et al., ; Sousa et al., ). This is a common response in patients undergoing thoracic and abdominal surgery because these surgeries frequently cause a decrease in the respiratory mechanics, predisposing patients to complications (Silva, Gazzana, & Knorsts, ).…”
mentioning
confidence: 99%